2002
DOI: 10.1097/00005768-200205000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Contraction-induced muscle damage is unaffected by vitamin E supplementation

Abstract: We conclude that vitamin E supplementation (30 d at 1200 IU.d-1), which resulted in a 2.8-fold higher serum vitamin E concentration (P < 0.01), had no affect on indices of contraction-induced muscle damage nor inflammation (macrophage infiltration) as a result of eccentrically biased muscle contractions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
97
1
8

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(119 citation statements)
references
References 28 publications
9
97
1
8
Order By: Relevance
“…However, it must be stated that this may not be the case, as studies that have investigated the effects of antioxidant or antiinflammatory supplementation on strength recovery after eccentric exercise have demonstrated equivocal findings [5][6][7][8][9][10][11][12][13][14][15]. Indeed, some studies have shown a beneficial effect of antioxidant supplementation at lower dosages [11,12], while, at higher dosages, others have shown no effect [7] or detrimental effects [9]. Thus, it is unclear if attenuating postexercise oxidative stress or inflammation is a viable mechanism for the improvements in isometric strength observed in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, it must be stated that this may not be the case, as studies that have investigated the effects of antioxidant or antiinflammatory supplementation on strength recovery after eccentric exercise have demonstrated equivocal findings [5][6][7][8][9][10][11][12][13][14][15]. Indeed, some studies have shown a beneficial effect of antioxidant supplementation at lower dosages [11,12], while, at higher dosages, others have shown no effect [7] or detrimental effects [9]. Thus, it is unclear if attenuating postexercise oxidative stress or inflammation is a viable mechanism for the improvements in isometric strength observed in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…A goal of numerous studies has been to identify dietary supplements that accelerate recovery from a bout of intense eccentric exercise [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. Antioxidant and nonsteroidal antiinflammatory drugs (NSAIDs) have a negligible effect on strength recovery [5][6][7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oxidative injury after acute exercise can be prevented by the intake of antioxidants, such as vitamins C and E, carotenoids, or polyphenols, not only during exercise, but also on a daily basis [84][85][86][87][88][89][90][91]. In contrast, several studies have indicated that antioxidants do not affect muscle damage and the inflammatory response caused by strenuous exercise [92][93][94]. One possibility on reason of the different results is that the effect of antioxidants is likely to be differences of exercise conditions, such intensity of mechanical stress and oxygen uptake.…”
Section: Prevention Of Injury and Fatiguementioning
confidence: 99%
“…Οι εργασίες που μελέτησαν την επίδραση της λήψης αντιοξειδωτικών βιταμινών C και Ε μεμονωμένα ή συνδυαστικά για περιορισμό της μυϊκής βλάβης και του οξειδωτικού στρες μετά από έκκεντρη άσκηση έχουν να επιδείξουν αντικρουόμενα αποτελέσματα. Οι περισσότερες από αυτές τις εργασίες, όπως φαίνεται συνοπτικά στους Πίνακες 1, 2 και 3, αναφέρουν ότι η λήψη βιταμίνης C και βιταμίνης Ε, συνδυαστικά ή μεμονωμένα, μπορεί να έχει έστω κάποια θετική επίδραση σε κάποιο δείκτη μυϊκής απόδοσης και οξειδωτικού στρες σε κάποια χρονική στιγμή μετά από έκκεντρη άσκηση (Beaton, et al, 2002;Bryer & Goldfarb, 2006;Cannon, et al, 1991;Goldfarb, et al, 2005;Kaminski & Boal, 1992;Phillips, et al, 2003;Sacheck, et al, 2003;Shafat, et al, 2004) . Θα πρέπει ωστόσο να αναφερθεί ότι ενώ αυτές οι εργασίες αναφέρουν θετική επίδραση της λήψης βιταμινών σε ένα δείκτη σε κάποιο χρονικό σημείο, στην ίδια εργασία κάποιος άλλος δείκτης δεν είχε υποστεί καμιά επίδραση από τη λήψη των βιταμινών.…”
Section: Petersen Et Al 2001unclassified